Influence of Working from Home Culture on the Effectiveness of Virtual Onboarding of New Employees - Esha, Zarin Tasnim; Hafiz, Nusrat; Islam, Md. Asadul (Society & Sustainability, 2023)
The COVID-19 pandemic remains a global disaster with extraordinary consequences for corporations and their people. The stresses of working from home during a pandemic are heightened for newbies entering new occupations and organizations. To address the issues concerning the rapid adoption of virtual onboarding in employment relations and human resource management practices, the paper seeks to determine whether there is a positive relationship between online orientation and training and holistic support with virtual onboarding in the context of multinational companies operating in Bangladesh. A cross-sectional survey of 110 individuals of diverse profiles from various multinational companies (MNCs) in Bangladesh is undertaken using Google Forms. The data was analyzed using SPSS 26.0. It was discovered that online orientation, online training, and holistic support play an important part in carrying out a successful virtual onboarding process for newcomers working from home. It was also found that having a strong relationship with peers, and senior coworkers is a key aspect of obtaining the assistance that new employees require in the workplace as they start. It is expected that the managers in the MNCs may regain workers’ trust by strengthening their virtual or onboarding operations as a whole. The frameworks offered can guide managers in better responding to employees’ needs. The successful use of virtual onboarding among the MNCs in Bangladesh is a little-explored research domain. The study findings address the gap by highlighting its effectiveness and encouraging the implication of virtual onboarding of the employees working from home in the MNCs. The study does not rule out the potential of other factors influencing virtual onboarding effectiveness, nor focus on any particular professional groups. The online survey makes it difficult to provide information on the sample’s representativeness. Further research and inquiry are required to confirm the findings.